Pathways to knowledge and inquiry learning - Pappas, Marjorie, 1938-; Tepe, Ann E., 1946- (Greenwood Village, CO : Libraries Unlimited, 2002)
Presents an introduction to the Pathways to Knowledge model of inquiry-based learning, discussing constructivism and contemporary curriculum design, information literacy, and collaboration; looking at how technology might be used by students in the information-seeking process, and offering advice to educators on how to implement inquiry learning into the curriculum.
Includes bibliographical references and index.
Library Media Connection.
Reference and Research Book News.
Professional
Keywords: Information retrieval -- Study and teaching; Inquiry (Theory of knowledge); Questioning; Information retrieval -- Study and teaching; Teaching; Theory of knowledge